Better alone? Assessing women empowerment after a family member migrates - Ceballos, Francisco; Domínguez, Ana Sofía; Heckert, Jessica; Hernandez, Manuel A.; Paz, Florencia (CGIAR System Organization, 2025)
This study explores how household migration—domestic or international—affects women’s empowerment in Honduras. Using panel data from 1,209 households collected over three years (2023–2025), we implement two main approaches: (i) a between-household comparison using endline cross-sectional data, relying on three alternative strategies to reduce selection bias, and (ii) a within-household difference-indifferences analysis tracking changes in empowerment metrics for the same women over time. The former analysis shows important gains in instrumental agency after a household member migrates internationally, but no measurable changes when a household member migrates domestically. In contrast, the within-household analysis finds no significant improvements and even some negative effects in collective agency and agency-enabling resources. Our findings highlight the complexity of migration’s effect on women’s empowerment, underscoring the importance of distinguishing between different types of migration when analyzing these effects and the need for high-quality longitudinal data to support plausibly causal interpretations.